If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 10 + -7x + 20x + 6 = 16x + 2 + -5x + -3x + 10 + -2x Reorder the terms: 10 + 6 + -3x + -7x + 20x = 16x + 2 + -5x + -3x + 10 + -2x Combine like terms: 10 + 6 = 16 16 + -3x + -7x + 20x = 16x + 2 + -5x + -3x + 10 + -2x Combine like terms: -3x + -7x = -10x 16 + -10x + 20x = 16x + 2 + -5x + -3x + 10 + -2x Combine like terms: -10x + 20x = 10x 16 + 10x = 16x + 2 + -5x + -3x + 10 + -2x Reorder the terms: 16 + 10x = 2 + 10 + 16x + -5x + -3x + -2x Combine like terms: 2 + 10 = 12 16 + 10x = 12 + 16x + -5x + -3x + -2x Combine like terms: 16x + -5x = 11x 16 + 10x = 12 + 11x + -3x + -2x Combine like terms: 11x + -3x = 8x 16 + 10x = 12 + 8x + -2x Combine like terms: 8x + -2x = 6x 16 + 10x = 12 + 6x Solving 16 + 10x = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 16 + 10x + -6x = 12 + 6x + -6x Combine like terms: 10x + -6x = 4x 16 + 4x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 16 + 4x = 12 + 0 16 + 4x = 12 Add '-16' to each side of the equation. 16 + -16 + 4x = 12 + -16 Combine like terms: 16 + -16 = 0 0 + 4x = 12 + -16 4x = 12 + -16 Combine like terms: 12 + -16 = -4 4x = -4 Divide each side by '4'. x = -1 Simplifying x = -1
| (2x-y-1)dx+(y-1)dy=0 | | 9+r=6 | | 4(x+7)=5x+8 | | 6x^2+1x-23=0 | | cos(t)=3 | | 16x^2-y^2-32x-6y+11=68 | | 7=-3c-2-24 | | d-4.6=-11.6 | | 2x-10+3x-7+5x=3x+3-3+3x-7+5x | | 35-5(2x-5)+20=-68 | | 0.2+1= | | X(over)4-9=3 | | -6x+10(-6)=-18 | | -2x-3+8x-18+5x=15-20-2x-3 | | 52+5=0 | | n(n-2)+2n(n+2)=16 | | 5.75=4.6y | | .4(7x+3)=40 | | -9(a-5)=18 | | 7b^2+15b+2=0 | | -2.4p=-2.88 | | 3t=2 | | 200-16x+100=24x-280+100 | | 4-x=2x+3x-5x | | -2t=6.3 | | v^2=u^2+2 | | 0.4n=2 | | 27+27x=351-9x | | 2y-7y=40 | | a-5.3=1.1 | | 9=p-8 | | .05x+3.11=.03x+3.03 |